2008
DOI: 10.1103/physrevlett.101.153602
|View full text |Cite
|
Sign up to set email alerts
|

Joint Temporal Density Measurements for Two-Photon State Characterization

Abstract: We demonstrate a new technique for characterizing two-photon quantum states based on joint temporal correlation measurements using time-resolved single-photon detection by femtosecond upconversion. We measure for the first time the joint temporal density of a two-photon entangled state, showing clearly the time anti-correlation of the coincident-frequency entangled photon pair generated by ultrafast spontaneous parametric down-conversion under extended phase-matching conditions. The new technique enables us to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 19 publications
1
97
0
Order By: Relevance
“…If the two entangled squeezed modes are generated in a factorizable state, we should see that the joint spectral probability distribution is also factorizable [8,9]. In the lowsqueezing limit, where a single photon pair is generated, it was recently shown that it is possible to generate pairs with an effective mode number that is close to the ideal value of 1 [8][9][10][11][12][13][14][15]. Hong-Ou-Mandel interference provides a measure of the similarity of the spectral distributions of the signal and idler modes.…”
Section: Introductionmentioning
confidence: 99%
“…If the two entangled squeezed modes are generated in a factorizable state, we should see that the joint spectral probability distribution is also factorizable [8,9]. In the lowsqueezing limit, where a single photon pair is generated, it was recently shown that it is possible to generate pairs with an effective mode number that is close to the ideal value of 1 [8][9][10][11][12][13][14][15]. Hong-Ou-Mandel interference provides a measure of the similarity of the spectral distributions of the signal and idler modes.…”
Section: Introductionmentioning
confidence: 99%
“…As spectral intensity measurements can be determined both by time-of-flight dispersive fiber spectrometers [8] and commercially available single photon sensitive spectrometers, one only needs a means of temporal intensity characterisation. Among these are homodyne detection [9,10], streak cameras [11,12] and ultrafast sampling using sum-frequency generation (SFG) [13,14]. Temporal measurements by upconversion sampling are particularly interesting because they can in principle be highly efficient and therefore of measure the temporal envelope with a short integration time.…”
Section: Introductionmentioning
confidence: 99%
“…However, direct JTI measurements are limited in time-resolution because of the detector jitter. While time-resolved frequency upconversion [37] and intensity modulation [8] schemes allow JTI measurements with picosecond resolution by effectively introducing narrow filters in time or frequency, they require a two-dimensional scan of the filter position(s) for a two-photon state and therefore, can be extremely slow. In the following, we demonstrate that a time-lens expands the two-photon temporal wavefunction while preserving the quantum correlations of the wavefunction.…”
Section: B Measurement Of Temporal Correlationsmentioning
confidence: 99%